Situational context directs how people affectively interpret robotic non-linguistic utterances - Read, Robin; Belpaeme, Tony (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
This paper presents an experiment investigating the influence that a situational context has upon how people affectively interpret Non-Linguistic Utterances made by a social robot. Subjects were presented five video conditions showing the robot making both a positive and negative utterance, the robot being subject to an action (e.g. receiving a kiss, or a slap), and then two videos showing the combination of the action and the robot reacting with both the positive and negative utterances. For each video an affective rating of valence was provided based upon how the subjects thought the robot felt given what had happened in the video. This was repeated for 5 different action scenarios. Results show that the affective interpretation of an action appears to override that of an utterance, regardless of the affective charge of the utterance. Furthermore, it is shown that if the meaning of the action and utterance are aligned, the overall interpretation is amplified. These findings are considered with respect to the practical use of utterances during social HRI.